A "Swedish" actuarial balance for a notional defined contribution pension scheme with disability and minimum pension benefits. (30th October 2017) - Pérez‐Salamero González, Juan M.; Ventura‐Marco, Manuel; Vidal‐Meliá, Carlos
Abstract: This article proposes a "Swedish" type actuarial balance sheet (ABS) for a notional defined contribution (NDC) scheme with disability and minimum pension benefits. The proposed ABS splits the pension system in two parts: the pure NDC part and the redistributive part, which includes the assets and liabilities originating from non‐contributory rights. The article contains a numerical example that sheds light on the real applicability of our proposal. The model has practical implications that could be of interest to policy‐makers, given that it integrates actuarial and social aspects of public pensions and discloses the real cost of redistribution through minimum pensions.